Composting of Banana Leaves and Coconut Leaves Using EM4 Bioactivator - Ulhasanah, Nova; Sarwono, Ariyanti; Yosafaat, Michael; Filippi, Dennis; Suryawan, I Wayan Koko; Wijaya, I Made Wahyu (Advances in Tropical Biodiversity and Environmental Sciences, 2022)
The generation of organic waste is one of the biggest problems in developing countries like Indonesia. Examples of organic waste that can be obtained, such as leaves, include banana leaves and coconut leaves. One way to process waste that can generally be done is by composting. In the composting process, a bioactivator such as EM4 is needed to accelerate the reaction process in the waste. This study aimed to determine the effectiveness of EM4 bioactivator in the degradation process of banana leaf and coconut leaf waste. Measurement of processing quality is measured in-situ with parameters of temperature, pH, and humidity. The waste temperature increased above 32oC for the addition of EM4 bioactivator, while without the addition of bioactivator it only increased to 31oC. pH tended to be in normal conditions and was in an acidic state on day 12. Humidity decreased from the beginning of the waste process to the end of the process. The final result of composting quality has met the criteria of SNI 19-7030-2004. There was also a decrease in the C/N content during the process, adjusting to soil conditions. The decrease in the value of C/N on the addition of bioactivator also influences the composting process.